UJI ANGKAT BIJI â BIJIAN PERTANIAN DALAM PIPA VERTIKAL DENGAN PENGARUH KECEPATAN HEMBUSAN UDARA DAN PANJANG PIPA HORIZONTAL SEBAGAI DASAR PERANCANGAN PEMINDAHAN BAHAN SECARA PNEUMATIK - , GALIH KUSUMA AJI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Air conveyors can be used to transfer materials quickly and often used to transfer material vertically. Percentage of materials catched in pneumatic transfer are influenced by several things. This study aim to determine the effect of horizontal pipe length, the air flow speed and the kinds of grain to the percentage of material catched. This study uses air velocity variation of 31.68 m / s